O Núcleo de Trabalho, Pesquisa e Práticas Sociais e a Cultura de Paz em escolas de territórios do Pacto por um Ceará Pacífico - Fortaleza (CE) - Freitas, Anna Cecília Cavalcante (2024)
This work focuses on the study of the Center of Work, Research, and Social Practices (NTPPS), aiming to investigate its contributions to the construction of a Culture of Peace within the school environment, specifically in two Full-Time High Schools within the state education network of Ceará, located in areas served by the Pacto por um Ceará Pacífico (Pact for a Peaceful Ceará) program. For this purpose, the study was divided into two moments. In the first, a content analysis of some Lesson Plans of NTPPS was conducted to identify themes and methodologies related to the Culture of Peace that are integrated into the high school curriculum. The second consisted of a case study in the mentioned schools, with students and teachers as participants from the NTPPS of the 1st grade, as well as representatives from the teaching staff and management staff of the educational units. Data collection techniques included observations of school activities, questionnaires, and semi-structured interviews with the mentioned subjects, analyzed through phenomenological reduction. The analysis of lesson plans revealed that, within the school curriculum dimension, NTPPS incorporates themes and methodologies related to Peace Education. However, the reflections proposed in the classes are confined to the microenvironment of the school, with no space for studying and reflecting on social and political issues from a broader societal perspective. The field research showed that the curriculum tends to be well-received by the majority of students, and the activities contribute to the Culture of Peace by fostering interpersonal interactions, promoting dialogue, respecting diversities, and supporting the self-awareness and self-realization process of teachers and students. However, the results also indicated that a significant number of students do not fully benefit from the potential of development that NTPPS can provide, and teacher training has been insufficient to support and guide teachers who are implementing the proposal in the classroom. This study is based on the contributions of Konzen (2019), Gadotti (2009), Abed (2014), Demo (2006), Freire and Shor (1986), as well as Jares (2002), Milani (2003), and Rabbani (2003).